2019
DOI: 10.20944/preprints201906.0055.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applying ANN, ANFIS, and LSSVM Models for Estimation of Acid Solvent Solubility in Supercritical CO2

Abstract: In the present work, a novel and the robust computational investigation is carried out to estimate solubility of different acids in supercritical carbon dioxide. Four different algorithms such as radial basis function artificial neural network, Multi-layer Perceptron (MLP) artificial neural network (ANN), Least squares support vector machine (LSSVM) and adaptive neuro-fuzzy inference system (ANFIS) are developed to predict the solubility of different acids in carbon dioxide based on the temperature, pressure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Finally, sensitivity analysis was used to determine the effect of different input parameters on the target parameter. More details about this analysis are given elsewhere [49,50]. According to Figure 5, it was found that T tot has the most direct effect on the target parameter, which corresponds to the relevancy factor (r) equal to +0.26, while other input parameters showed an inverse effect on the target parameter so that GLS showed the most negative effect with r equal to -0.85.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, sensitivity analysis was used to determine the effect of different input parameters on the target parameter. More details about this analysis are given elsewhere [49,50]. According to Figure 5, it was found that T tot has the most direct effect on the target parameter, which corresponds to the relevancy factor (r) equal to +0.26, while other input parameters showed an inverse effect on the target parameter so that GLS showed the most negative effect with r equal to -0.85.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the leaf flexible hinge is selected for the mechanism. To select appropriated dimensions for the mechanism, this investigation proposes a hybrid Taguchi approach based on grey relational analysis and neural network with fuzzy logic and ANFIS algorithms [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…At the provincial level, the deep neural network assists in managing a lot of supplementary data [32]. For modeling and uncertainty analysis of groundwater levels, the adaptive neuro-fuzzy interface system with the grasshopper optimization algorithm and support vector machine exhibits the best and worst results, respectively [33]. The best methods for estimating the solubility of acids in supercritical carbon dioxide are provided by the radial basis function artificial neural network, multi-layer perceptron artificial neural network, least squares support vector machine, and adaptive neuro-fuzzy inference system.…”
Section: Introductionmentioning
confidence: 99%